Efficacy of Disinfection of Dental Stone Casts: Virkon versus Sodium Hypochlorite - Elnaz Moslehifard; Farzaneh Lotfipour; Mahmood Robati Anaraki; Elnaz Shafee; Shabnam Tamjid-shabestari; Tahereh Ghaffari (Tehran University of Medical Sciences, 2015)
Objectives: The purpose of this experimental study was to compare the disinfection efficacy of sodium hypochlorite and peroxygenic acid (Virkon) solutions for dental stone casts contaminated with microbial strains. Materials and Methods: A total of 960 spherical stone beads with a diameter of 10 mm were prepared and used as carriers of bacterial inoculums. They were individually inoculated by soaking in broth culture media containing each of the four understudy microorganisms. Different concentrations of Virkon and hypochlorite solutions were prepared using distilled water and then were sprayed on the surfaces of dental casts contaminated with Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis and Candida albicans. The pour plate technique was used to evaluate the antimicrobi- al efficacy of each solution. Microbicidal effect (ME) was calculated according to the log10 of control colony counts minus the log10 of the remaining colony counts after the antimicrobial procedure. Statistical difference was assessed using the Kruskal Wallis and the Man Whitney U tests with a significance of 95%. Results: We observed different bactericidal effects of Virkon at various concentra- tions; 1% Virkon killed S. aureus, P aeruginosa, and Candida albicans, while 3% Virkon solution was required to kill B. subtilis. For S. aureus, P. aeruginosa, and C. albicans, no significant difference was observed between1% Virkon and 0.525% so- dium hypochlorite (P >0.05). For B. subtilis, the efficacy of 3% Virkon and 0.525%sodium hypochlorite was not significantly different (P >0.999). Conclusion: According to the obtained results for Virkon and based on its low toxici- ty and good environmental compatibility, it may be recommended as an antimicrobial disinfectant for dental stone casts as non-critical items.